Maintenance treatment with trofosfamide in patients with advanced soft tissue sarcoma – a retrospective single-centre analysis - Anton Burkhard-Meier; Vera Valerie Rechenauer; Luc M. Berclaz; Vindi Jurinovic; Markus Albertsmeier; Hans Roland Dürr; Sinan E. Güler; Michael Hoberger; Alexander Klein; Thomas Knösel; Wolfgang G. Kunz; Nina-Sophie Schmidt-Hegemann; et al. (Acta Oncologica)
Background: The prognosis of patients with advanced soft tissue sarcoma (STS) remains dismal. Trofosfamide (TRO) has been proposed as a well-tolerated oral maintenance therapy. This retrospective analysis aims to determine the value of this therapy.